Challenges to Online Disability Rights Advocacy in India - Kaur, Sukhnidh; Manohar, Swami; Bali, Kalika; Vashistha, Aditya (CHI 2024, 2024)
People with disabilities experience high levels of social discrimination worldwide. But, these harms are more pronounced in the Global South due to the intense stigma around disability and its intersections with structural embeddings of patriarchy. The massive growth of social media in the Global South provides people with disabilities a unique opportunity to advocate for disability rights and challenge regressive ableist norms. Yet, little is known about the challenges they face in doing their advocacy work on social media. Through interviews with 20 disability advocates in India with diverse gender identities and abilities, we found that disability advocates routinely face ableist hate and harassment, patronizing and invalidating comments, and lack of visibility and support, which forces them to self-censor as a form of self-protection, leading to low advocacy outcomes. We draw on these findings to illuminate the role of social media in the invisibilization of people with disabilities in the online sphere.